2018
DOI: 10.1105/tpc.18.00528
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid Directly Regulates PINOID-Dependent Phosphorylation and Activation of the PIN-FORMED2 Auxin Efflux Transporter in Response to Salt Stress

Abstract: Remodeling of auxin distribution during the integration of plant growth responses with the environment requires the precise control of auxin influx and efflux transporters. The plasma membrane-localized PIN-FORMED (PIN) proteins facilitate auxin efflux from cells, and their activity is regulated by reversible phosphorylation. How PIN modulates plant cellular responses to external stresses and whether its activity is coordinated by phospholipids remain unclear. Here, we reveal that, in Arabidopsis (Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 101 publications
(183 reference statements)
4
102
0
1
Order By: Relevance
“…PLD‐derived PA plays crucial roles in plant responses to various environmental stresses, such as salinity and P deficiency (Li et al , ; Wang et al , ). PA interacts with protein kinase PID and increases the PID‐dependent phosphorylation of PIN2, which enhances the auxin efflux activity and PIN2 accumulation at the plasma membrane under salt stress (Wang et al , ). Our results demonstrated that PLDζ2‐derived PA that is induced by P deficiency mediates the vacuolar degradation of PIN2 to increase the plant response to low P tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLD‐derived PA plays crucial roles in plant responses to various environmental stresses, such as salinity and P deficiency (Li et al , ; Wang et al , ). PA interacts with protein kinase PID and increases the PID‐dependent phosphorylation of PIN2, which enhances the auxin efflux activity and PIN2 accumulation at the plasma membrane under salt stress (Wang et al , ). Our results demonstrated that PLDζ2‐derived PA that is induced by P deficiency mediates the vacuolar degradation of PIN2 to increase the plant response to low P tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…PLD-derived PA plays crucial roles in plant responses to various environmental stresses, such as salinity and P deficiency (Li et al, 2006;Wang et al, 2019). PA interacts with protein kinase PID and increases the PID-dependent phosphorylation of PIN2, which enhances the auxin efflux activity and PIN2 accumulation at the plasma membrane under salt stress (Wang et al, 2019).…”
Section: Phosphatidic Acid or Phosphorus Deficiency Suppresses Vacuolmentioning
confidence: 99%
“…[55,57,58] Besides, PIN proteins have also been reported to be phosphorylated by MITOGEN-ACTIVATED PRO-TEIN KINASEs (MPKs), which inhibit the polar targeting and thus the function of PINs. [55,57,58] Besides, PIN proteins have also been reported to be phosphorylated by MITOGEN-ACTIVATED PRO-TEIN KINASEs (MPKs), which inhibit the polar targeting and thus the function of PINs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of genetic evidence suggest that the local membrane status regulates polar localization and recycling of PIN proteins. For example, mutants defective in phospholipid biosynthesis or metabolism exhibit strong defects in various growth and developmental processes, for which mislocalization of PIN proteins account for many of those phenotypes 19, 4853 . Our studies uncover a novel layer of participation of lipids, in regulating PIN transporters, at the level of activity via polarizing a PDK1-mediated phosphorylation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PID, D6PKs and PAX phosphorylate basal-localized PINs to regulate their activity 17 . To date, little is known about the upstream regulatory mechanism by which this phosphorylation increases or declines, except for that both PID 18, 19 and D6PK 20 have been reported to bind phospholipids, which might determine their subcellular localizations.…”
Section: Introductionmentioning
confidence: 99%